2017
DOI: 10.1021/acs.inorgchem.7b02263
|View full text |Cite
|
Sign up to set email alerts
|

Raman and Density Functional Theory Studies of Li2Mo4O13 Structures in Crystalline and Molten States

Abstract: The LiMoO melt structure and its Raman spectral characteristics are the key for establishing the composition-structure relationship of lithium molybdate melts. In this work, Raman spectroscopy, factor group analysis, and density functional theory (DFT) were applied to investigate the structural and spectral details of the H-LiMoO crystal and a LiMoO melt. Factor group analysis shows that the crystal has 171 vibrational modes (84A + 87A), including three acoustic modes (3A), six librational modes (2A + 4A), 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…We also observed the formation of such species by XRD ( Figure 6). We tentatively assign the Raman bands at 289 cm −1 and 891 cm −1 to the bending and symmetric stretching modes of the terminal Mo-Ot bond in a well-defined Li2Mo4O13 phase, while other Raman bands expected for Li2Mo4O13 (160-420 cm −1 , 420-746 cm −1 , and 845-991 cm −1 ) [54] were not clearly detected. We hence suggest in catalysts with 7.1 wt % MoO3 the possible presence of Li2Mo4O13 polymolybdate species.…”
Section: Raman Spectramentioning
confidence: 72%
“…We also observed the formation of such species by XRD ( Figure 6). We tentatively assign the Raman bands at 289 cm −1 and 891 cm −1 to the bending and symmetric stretching modes of the terminal Mo-Ot bond in a well-defined Li2Mo4O13 phase, while other Raman bands expected for Li2Mo4O13 (160-420 cm −1 , 420-746 cm −1 , and 845-991 cm −1 ) [54] were not clearly detected. We hence suggest in catalysts with 7.1 wt % MoO3 the possible presence of Li2Mo4O13 polymolybdate species.…”
Section: Raman Spectramentioning
confidence: 72%
“…19 Therefore, in addition to XRD, Raman spectroscopy (Figure 2) was used to carefully assess the phase purity by investigating the vibrational modes of the lattice. The Raman spectrum of the molybdenum oxide can be divided into three regions: 22 Figure 2 presents the Raman spectra of Li 2 Mo 4 O 13 , which shows multiple strong peaks in the high-frequency region from 800 to 1000 cm −1 that corresponds to Mo�O stretching modes (1001, 990, 973, 947, 921, 913, 899, and 853 cm −1 ). A large number of peaks in this regime result from the combination of multiple octahedral coordination environments.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This ternary lithium molybdenum oxide has been reported previously, 18−20 but its electrochemistry has not yet been well characterized. 21,22 Here, we prepare and characterize this compound using electrochemistry, X-ray diffraction, and UPS. UPS measurements support the hypothesis that the addition of electropositive Li to the structure pushes the Mo d-electrons closer to the vacuum level.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In general, these inorganic materials that show low phonon energies are preferable for luminescent hosts since they can efficiently decrease the ratio of nonradiative transition and boost the luminescent efficiency . Compared with other developed inorganics, the molybdates with a representative structure of scheelite are considered as potential candidates for luminescent hosts owing to their immanent optical properties (i.e., strong absorption in the ultraviolet [300‐350 nm] region originating from the O 2‒ → Mo 6+ transition) and proper phonon energy . Cao et al revealed that the Sm 3+ ‐activated LiLaMo 2 O 8 phosphors can emit visible red emission under the excitation of NUV light .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Compared with other developed inorganics, the molybdates with a representative structure of scheelite are considered as potential candidates for luminescent hosts owing to their immanent optical properties (i.e., strong absorption in the ultraviolet [300-350 nm] region originating from the O 2-→ Mo 6+ transition) and proper phonon energy. 14,15 Cao et al revealed that the Sm 3+ -activated LiLaMo 2 O 8 phosphors can emit visible red emission under the excitation of NUV light. 16 Jeong et al reported that the Sr 2 CaMoO 6 :Sm 3+ phosphor which showed potential application in WLEDs can be simultaneously excited by the NUV and blue light.…”
Section: Introductionmentioning
confidence: 99%